Le mouvement de santé en français en contexte linguistique minoritaire : les représentations des acteurs sur l'avenir des services - Bouchard, Louise (Revue canadienne de sociologie, 2011)
Le plan d'action pour les langues officielles lancé en 2003 projette de revitaliser la dualité linguistique du pays. Parmi les domaines prioritaires, la santé se voit privilégier dans le but d'assurer la formation des professionnels de la santé pour desservir les communautés de langue officielle minoritaire et de réseauter les principaux acteurs préoccupés par l'organisation des services dans la langue minoritaire. L'objectif de cet article est de rendre compte des représentations des francophones en situation linguistique minoritaire eu égard à l'avenir des services de santé en français. L'étude repose sur une méthodologie participative: la cartographie conceptuelle permettant de recenser l'univers conceptuel d'une problématique donnée.

Les services de santé en français en Ontario: Offre - demande - utilisation - Gagnon-Arpin, Isabelle; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2011)

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)

Aînés francophones et intervenants multiethniques en santé : un projet de formation interculturelle adapté aux collègues francophones canadiens - Parent, R.; Bouchard, Louise; Lebel, M. (Reflets, 2014)

Success strategies for linguistically competent healthcare: The magic bullets and cautionary tales of active offer of French-language health services in Ontario - Farmanova, Elina; Bouchard, Louise; Bonneville, Luc (Healthcare Quaterly, 2018)
An active offer of French-language health services (FLHS) was introduced in several Canadian provinces to help create an environment that will anticipate the needs of Francophones in their community and will stimulate the demand for services in French. For the active offer to be implemented, changes in how health services are organized and managed at both organizational and system levels must be introduced. In this perspective paper, we identify several success strategies and potential pitfalls with regards to the implementation of the active offer of FLHS primarily at the level of healthcare organization. Our recommendations are based on a recent health services research study exploring reorganization and management strategies for the delivery of the active offer of FLHS in Ontario and insights from a focus group with healthcare administrators conducted as part of this research. We propose a "wrap-around strategy" called organizational health literacy to help reorient organizational culture and improve management and sustainability of the active offer of FLHS. These strategies have relevance for advocates and professionals working to promote an active offer of FLHS, including healthcare administrators, human resource professionals, quality-improvement specialists and others.

Active offer of health services in French in Ontario: Analysis of reorganization and management strategies of health-care organizations - Farmanova, Elina; Bonneville, Luc; Bouchard, Louise (The International Journal of Health Planning and Management, 2018)
The availability of health services in French is not only weak but also inexistent in some regions in Canada. As a result, estimated 78% of more than a million of Francophones living in a minority situation in Canada experience difficulties accessing health care in French. To promote the delivery of health services in French, publicly funded organizations are encouraged to take measures to ensure that French-language services are clearly visible, available, easily accessible, and equivalent to the quality of services offered in English. Objective This study examines the reorganization and management strategies taken by health care organizations in Ontario that provide health services in French. Methods Review and analysis of designation plans of a sample of health care organizations. Results Few health care organizations providing services in French have concrete strategies to guarantee availability, visibility, and accessibility of French-language services. Conclusions Implementation of the active offer of French-language services is likely to be difficult and slow. The Ontario government must strengthen collaboration with health care organizations, Francophone communities, and other key actors participating in the designation process to help health care organizations build capacities for the effective offer of French-language services.

L’ambition territoriale dans le dossier de la santé en français - Gilbert, Anne; Lefebvre, Marie; Bouchard, Louise (Francophonies d’Amérique, 2010)
Dix ans se sont écoulés depuis le jugement Montfort, qui consacrait l’Hôpital comme une composante essentielle de la vitalité des communautés francophones en situation minoritaire. Jusqu’à quel point cette reconnaissance du droit à un service en français, accessible dans des établissements localisés dans les milieux dans lesquels la minorité évolue, a-t-elle mené à une ambition plus territoriale chez les intervenants francophones ? L’analyse des propos tenus par 38 participants à un exercice de cartographie conceptuelle sur l’avenir des services de santé en français en Ontario révèle qu’ils ne s’aventurent pas très loin sur le terrain des modalités de l’édification d’un véritable territoire francophone en santé. L’institution est évoquée, mais davantage comme un projet appartenant à un horizon lointain que comme un enjeu actuel. En guise de conclusion, les auteures se sont interrogées sur les effets d’une telle vision sur l’avenir des services de santé en français.

L'offre active des services de santé en français en Ontario : une mesure d'équité - Bouchard, Louise; Beaulieu, Marielle; Desmeules, Martin (Reflets, 2012)
Cet article fait état d’une recherche sur l’offre active de services en français en Ontario. L’étude avait pour objectifs de recenser les définitions de l’offre active de services en français; d’identifier les pratiques d’offre active (facilitateurs ou obstacles); d’identifier les indicateurs de mesure de l’offre active et de proposer des recommandations permettant d’améliorer l’offre active de services en français. À cette fin, une revue documentaire, une enquête auprès de professionnels oeuvrant dans le domaine de la planification des services de santé en français ainsi qu’un atelier de cartographie conceptuelle ont été entrepris. Mots-clés : minorité linguistique, services de santé, offre active, Loi 8

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Un aperçu de la santé et de ses déterminants dans la région Champlain de l’Est de l’Ontario d’après les données des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) 2001-2003-2005-2007 - Gagnon-Arpin, Isabelle; Gaboury, Isabelle; Bouchard, Louise (Université d'Ottawa, Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada, Institut de recherche sur la santé des population, 2009)

Portraits socio-sanitaires des communautés francophones de l'Ontario | Demographic and health profiles of Ontario's Francophone communities - Gagnon-Arpin, Isabelle; Sedigh, Golnaz; Bouchard, Louise (Alliance des réseaux ontariens de santé en français, 2011)

La santé des personnes âgées francophones vivant en situation minoritaire au Canada : enjeux et besoins - Bouchard, Louise; Desmeules, Martin (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé L’objectif de ce chapitre est de présenter le profil sociodémographique et sanitaire de la population aînée francophone (65 ans et plus) vivant en situation linguistique minoritaire afin d’en ressortir les enjeux et les besoins qui la caractérisent. Nous aborderons dans un premier temps le fait minoritaire et son effet potentiel sur le vieillissement de la population et la position sociale des personnes âgées, leur santé et leur accès aux services. Une seconde section établira, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes (ESCC, cycles combinés, 2003-2012), le portrait sociosanitaire des aînés en fonction de trois grandes régions canadiennes (les provinces de l’Atlantique, l’Ontario et les provinces de l’Ouest). Enfin, nous discuterons ici de deux enjeux qui nous apparaissent fondamentaux au regard de cette population minoritaire, soit celui de la littératie en santé, c’est-à-dire la capacité de communiquer et de naviguer adéquatement dans le système de santé, et celui de l’offre active de services, une mesure d’équité et de qualité des soins. Mots-clés : aînés francophones, minorités linguistiques, portrait sociosanitaire, Canada, Enquête sur la santé dans les collectivités canadiennes (ESCC).

The health of Francophone seniors living in minority communities in Canada: Issues and needs - Bouchard, Louise; Desmeules, Martin (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Étude sur les populations âgées et l’accès aux soins de longue durée en français en Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)
Ce rapport présente une analyse de la demande et de l’offre de services de santé en français (SSF) dans le secteur des soins de longue durée (SLD) en Ontario. En nous appuyant sur des données publiques ainsi que sur des données administratives fournies par le ministère de la Santé de l’Ontario, le rapport examine : 1. la demande régionale de SSF, évaluée selon la population ontarienne âgée de 65 ans et plus et la population francophone de ce groupe d’âge ; 2. l’offre de SSF, mesurée par le nombre et le type de foyers présents dans chaque région, ainsi que par les compétences linguistiques en français de leur personnel.

Study of aging populations and access to French-language long-term care in Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)

Les aînés francophones de l’Ontario : un portrait de santé. - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)

Francophone seniors in Ontario: A health portrait - Bouchard, Louise; Makvandi, E.; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

The health of Francophone men and women in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario & University of Ottawa, 2014)

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Besoins et services en français en matière de sexopérinatalité chez les couples parentaux franco-ontariens - de Pierrepont, Catherine; Polomeno, Viola; Bouchard, Louise; Reissing, Elke (Minorités linguistiques et société, 2017)
Cet article dévoile un portrait des besoins et des services en français en matière de sexopérinatalité perçus par 67 couples parentaux francophones en situation linguistique minoritaire d’Ottawa et de l’Est de l’Ontario. Les couples ont des besoins d’informations et de soutien ; pour eux, il est important d’aborder la sexualité pendant la période périnatale. Toutefois, le sujet est peu discuté avec les professionnels de la santé, et très peu de services sexopérinataux en français sont offerts, même s’ils sont souhaités par ces couples. Les discussions sur la sexualité qui se déroulent majoritairement en anglais constituent un obstacle supplémentaire pour une majorité des couples. Mots-clés : sexualité périnatale, couples parentaux, périnatalité, francophones en situation linguistique minoritaire, services de santé en français

Profil santé des communautés francophones minoritaires au Canada [infographie] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)
Contexte : Les communautés francophones vivant en situation minoritaire évaluées à 1 million de personnes (4,4% de la population canadienne) sont dispersées un peu partout au pays. Les plus fortes concentrations sont en Ontario (509 265) et au Nouveau Brunswick (239 400), alors qu'ailleurs, on peut compter de 63 000 francophones (Alberta) à moins de 500 francophones (Nunavut). Ces communautés présentent un profil diversifié : elles sont en général moins jeunes, moins scolarisées, ont de plus faibles revenus. Elles sont davantage concentrés dans des régions où l'économie est plus instable rendant ainsi plus difficile le développement et l'accès aux ressources sociales. L'objectif de cette affiche est de présenter une sélection d'indicateurs décrivant certains aspects des déterminants de la santé de la population francophone en situation linguistique minoritaire. Méthode : Les indicateurs de santé sont extraits d'une analyse secondaire de l'ESCC combinant les cycles 2001, 2003 et 2005. L'analyse se fonde sur un échantillon d'adultes de 25 ans et plus de 244 382 : 12 583 francophones ; 256 966 anglophones. Le profil montre les situations et les déterminants les plus défavorables comparant la communauté minoritaire à la majorité anglophone dans l'ensemble du Canada excluant le Québec. Résultats : Sur l'ensemble des indicateurs sélectionnés (variables sociodémographiques, santé perçue, présence de maladie, difficulté à accomplir une tâche, services de santé, styles de vie, le sentiment d'appartenance), les communautés francophones présentent un profil de santé plus défavorable que la majorité anglophone et ce de façon plus marquée dans certaines zones géographiques. Conclusion : Les résultats permettent de soutenir que le rapport minoritaire/majoritaire semble traduire une inégalité sociale et d'accès aux ressources qui, traversée par les autres déterminants sociaux de la santé (statut socioéconomique, éducation et littératie, immigration) contribue de facto aux disparités de santé. Ils montrent l'importance d'approfondir et de mieux comprendre l'ensemble des déterminants de la santé ainsi que les interactions entre les contextes, les milieux de vie locaux, l'impact des politiques et la santé.

Health profile of French-speaking minority communities in Canada [infographic] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

Le surplus de poids chez les francophones et les anglophones - Gagnon-Arpin, Isabelle; Makvandi, Ewa; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs Des études récentes rapportent une prévalence d’embonpoint et d’obésité plus élevée chez les francophones en situation linguistique minoritaire en comparaison à la majorité anglophone du Canada. L’objectif de l’étude est de vérifier si l’appartenance au groupe linguistique minoritaire s’ajoute aux déterminants sociaux du surplus de poids. Méthode Les statistiques descriptives (n=128 986), provenant de cinq cycles de l’Enquête sur la santé dans les collectivités canadiennes, ont été croisées en fonction de la langue et du sexe des individus. Deux modèles de régression logistique multivariée, pour les hommes et pour les femmes, ont permis de tester l’association entre le surplus de poids et la langue en contrôlant pour les déterminants socioéconomiques et comportementaux. Résultats La prévalence du surplus de poids est plus élevée chez les francophones que chez les anglophones de l’Ontario, bien que cette différence ne soit plus significative lorsque le modèle est ajusté pour les caractéristiques socioéconomiques et comportementales. Néanmoins, les francophones sont plus âgés, moins éduqués et vivent davantage en milieu rural que leurs homologues anglophones, un contexte qui les rend plus vulnérables. Conclusion L’étude vient réaffirmer le rôle des déterminants sociaux et comportementaux dans la prévalence du surplus de poids. Bien que la langue n’influence pas directement le surplus de poids, compte tenu de la réalité socioéconomique de la minorité francophone, représentée en plus grande proportion dans les strates de la population plus vulnérable au surplus de poids, l’appartenance à un groupe minoritaire devrait interpeller les planificateurs de la santé.

Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario - Duong, Patrick; Batista, Ricardo; Lizotte, Mathieu; Sauvé-Schenk, Katrine; Bouchard, Louise (2024)

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (Colloque 103 – L’offre des services de santé dans les langues minoritaires, dans le cadre du 92e Congrès de l’Acfas, 2025)

Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (Colloque 103 – L’offre des services de santé dans les langues minoritaires, 92e Congrès de l’Acfas, 2025)

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.

Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie] - Gagnon-Arpin, Isabelle; Bouchard, Louise; Gaboury, Isabelle; Bourbonnais, V.; Chomienne, Marie-Hélène (2009)

Comment améliorer la santé des aînés francophones vieillissant en Ontario ? Entre approche populationnelle et santé communautaire - Bouchard, Louise; van Kemenade, Solange (La santé communautaire en 4 actes : repères, acteurs, démarches et défis, 2016)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)

La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)

Impact de la situation linguistique minoritaire sur les soins de santé pour des personnes âgées francophones de l'Ontario souffrant de maladies chroniques : une étude qualitative exploratoire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Consortium national de formation en santé, 2010)

Enquête exploratoire sur le recueil de la variable linguistique dans les données administratives des hôpitaux de la région du RLISS-Champlain - Chomienne, Marie-Hélène; LeClerc, Chantale; Schnarch, Brian; Bouchard, Louise; McKay, Martine; Farmanova, Elina (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, Réseau local d’intégration des services de santé de Champlain, 2011)

Comorbidités entre maladies chroniques et problèmes de santé mentale fréquents : différences entre francophones et anglophones - Grenier, Jean; Gosselin, Dominique; Greenman, Paul. Samuel; Chomienne, Marie-Hélène; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Psy-Cause, 2016)

The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.

Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.